Women after mastectomy in marriage and family life on the basis of empirical studies - Irzmańska-Hudziak, Anna; Małek, Beata Maria; Szadowska-Szlachetka, Zdzisława; Stasiak, Elżbieta; Muzyczka, Katarzyna Karolina; Stanisławek, Andrzej (Polish Journal of Public Health, 2011)
Introduction. The paper presents various aspects of functioning in a marriage, family and in the closest social environment of women after mastectomy due to breast cancer resulting in different types of difficulties occurring in many spheres of woman’s life (emotional, mental and physical, sexual and social). Moreover, the paper discusses a variety of ways of coping with these problems by these women in a life situation which is new and difficult to them. Aim. The objective of the paper is to present functioning in marriage and in family life of women who have undergone mastectomy. Material and methods. The survey carried out in 2006 covered 100 married women after mastectomy. They came mainly from Warsaw, Biała Podlaska, Radzyń Podlaski, Olsztyn and Lublin. The results were collected with the use of a questionnaire prepared by the authors. The respondents were women who had undergone mastectomy at least one year before. The surveyed were married women with children. Results. Women after mastectomy face various types of difficulties. These are problems associated with the past procedure, with additional treatment and self-care. The most frequently occurring symptoms after the surgery are formication and numbness of the limb on the operated side of the body (52%), pain connected with arm swelling (37%) and pains in spine (36%), together with the lack of physical strength and poor mood (35%). Women living in small towns required support. In turn, women from cities did not need help. Conclusions. A conclusion arises that the previous studies have mainly discussed issues connected with treatment, rehabilitation and complications following treatment. However, the problems associated with women’s functioning in marriage and family after mastectomy have been neglected (or they have not been noticed). Thus there is insufficient information in the Polish literature on the subject.